Punctuality and Economic Development: ความตรงต่อเวลาและการพัฒนาเศรษฐกิจ - Punyasavatsut, Arunee (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาวัฒนธรรมความตรงต่อเวลาในประเทศต่างๆ ส่งผลต่อการพัฒนาทางเศรษฐกิจของประเทศหรือไม่ เนื่องจากความตรงต่อเวลาทำให้ประสิทธิภาพการผลิตเพิ่มขึ้น การศึกษานี้ทำการคาดประมาณฟังก์ชันการผลิต โดยมีตัวแปรอิสระคือ ดัชนีความตรงต่อเวลา ปัจจัยการผลิตต่างๆ และตัวแปรควบคุม โดยมีสมมติฐานว่าความตรงต่อเวลามีผลในทางบวกต่อการพัฒนาทางเศรษฐกิจ ข้อมูลที่ใช้ในการศึกษาคือข้อมูลของ 217 ประเทศ ใน ค.ศ. 2014 จากการคาดประมาณฟังก์ชันการผลิตด้วยวิธีกำลังสองน้อยที่สุด ผลการศึกษาพบว่าความตรงต่อเวลาส่งผลต่อการพัฒนาเศรษฐกิจ โดยที่ประเทศที่มีวัฒนธรรมความตรงต่อเวลาจะมีรายได้ต่อประชากรสูงมากกว่า คำสำคัญ: ความตรงต่อเวลา ดัชนีความตรงต่อเวลา การพัฒนาเศรษฐกิจ แบบจำลองเจริญเติบโตทางเศรษฐกิจ ABSTRACT This research aimed to study whether the cultural perception of time, especially punctuality, contributes to the economic development of a nation by enhancing efficiency in production. In order to answer the research question, a production function was estimated. The explanatory variables included the index of punctuality, inputs of production, and control variables.–The hypothesis was that time punctuality has positive effects on economic development. The production function was estimated using the Ordinary Least Squares method using 217 country data in 2014. The results indicated that punctuality affects economic development. Countries with a greater time-punctuality culture yield higher per capita income. Keywords: Time Punctuality, Index of Punctuality, Economic Development, Growth Model